Tracheid and Pit Dimensions Hardly Vary in the Xylem of Pinus sylvestris Under Contrasting Growing Conditions - Held, Magdalena; Ganthaler, Andrea; Lintunen, Anna; Oberhuber, Walter; Mayr, Stefan (Frontiers in Plant Science, 2021)
Maintaining sufficient water transport via the xylem is crucial for tree survival under variable environmental conditions. Both efficiency and safety of the water transport are based on the anatomical structure of conduits and their connections, the pits. Yet, the plasticity of the xylem anatomy, particularly that of the pit structures, remains unclear. Also, trees adjust conduit dimensions to the water transport distance (i.e., tree size), but knowledge on respective adjustments in adjust pit dimensions is scarce. We compared tracheid traits [mean tracheid diameter d, mean hydraulic diameter dh, cell wall reinforcement (t/b)2], pit dimensions (diameters of pit aperture Da, torus Dt, margo Dm, and pit border Dp), and pit functional properties (margo flexibility F, absolute overlap Oa, torus overlap O, and valve effect Vef) of two Scots pine (Pinus sylvestris L.) stands of similar tree heights but contrasting growth rates. Furthermore, we analyzed the trends of these xylem anatomical parameters across tree rings. Tracheid traits and pit dimensions were similar on both sites, whereas Oa, O, and F were higher at the site with a lower growth rate. On the lower growth rate site, dh and pit dimensions increased across tree rings from pith to bark, and in trees from both sites, dh scaled with pit dimensions. Adjusted pit functional properties indicate slightly higher hydraulic safety in trees with lower growth rate, though a lack of major differences in measured traits indicated overall low plasticity of the tracheid and pit architecture. Mean hydraulic diameter and pit dimension are well coordinated to increase the hydraulic efficiency towards the outer tree rings and thus with increasing tree height. Our results contribute to a better understanding of tree hydraulics under variable environmental conditions.